Factors affecting the decision to visit Khlong Mae Kha, Mueang District, Chiang Mai Province of Thai tourists. - Pinta, Ladda; Yonakad, Arunrat (Journal of Management Science Nakhon Pathom Rajabhat University, 2025)
This research aimed to 1) study demographic factors influencing Thai tourists' decisions to visit Khlong Mae Kha in Mueang District, Chiang Mai Province; 2) investigate consumer behaviors affecting Thai tourists' decisions to visit Khlong Mae Kha; and 3) analyze tourism attraction factors influencing Thai tourists' decisions to visit Khlong Mae Kha. The sample comprised 400 Thai tourists visiting the aforementioned location, selected using an accidental sampling method. Data were collected via questionnaires and analyzed using descriptive statistics and inferential statistics, specifically t-tests, one-way ANOVA, and multiple linear regression analysis (Enter method). The result showed that 1. Demographic factors, specifically gender, occupation, and income, significantly influenced the decision to visit Khlong Mae Kha at a statistical significance level of .05. 2. Consumer behaviors related to travel companions, travel objectives, and pre-travel information sources also significantly differed at a statistical significance level of .05. 3. Factors influencing the decision to visit, specifically physical environment, reputation of the place, safety, and tourism resources, collectively accounted for 82.9% of the variance in the decision to visit. These factors positively influenced the decision. The regression equation derived from this analysis is as follows Decision to Visit Khlong Mae Kha (Thai Tourists) = 0.257 + (Physical Environment) + 0.088 (Reputation of Place) + (Safety) + 0.256 + 0.108 (Travel Aspect) + 0.380 (Tourism Resources) Article history: Received 5 February 2024 Revised 1 July 2025 Accepted 18 July 2025 SIMILARITY INDEX = 5.88 %